2017
DOI: 10.1371/journal.pone.0180230
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent aortic valve pathology in patients with rheumatic heart disease

Abstract: BackgroundRheumatic heart disease is an autoimmune disease caused by group A streptococci infection and frequently affects the aortic valve. Sex differences are common in the disease progression, treatment, and outcome. However, little is known about the sex differences in the pathology of aortic valves in rheumatic heart disease.DesignWe studied the end-stage calcific aortic valves from male versus female patients to reveal the sex-dependent pathology differences and molecular changes associated with requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, immunohistochemistry assays more comprehensively determine the role of inflammatory markers as compared to observational findings in our study, e.g., a recent study in China indicated the role of M1 macrophages in progressing atrial inflammation and thrombus formation in rheumatic MS patients with AF [29]. Finally, the small sample size hindered the observation of gender-based differences, such as the varied aortic valve pathology observed in a previous study [30].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, immunohistochemistry assays more comprehensively determine the role of inflammatory markers as compared to observational findings in our study, e.g., a recent study in China indicated the role of M1 macrophages in progressing atrial inflammation and thrombus formation in rheumatic MS patients with AF [29]. Finally, the small sample size hindered the observation of gender-based differences, such as the varied aortic valve pathology observed in a previous study [30].…”
Section: Discussionmentioning
confidence: 88%
“…In line with these results, enhanced apoptosis in men-derived AVs and VICs could be a source of apoptotic bodies that would enhance calcific phenotypes in men. Conversely, reduced apoptotic signals have been previously described in women diagnosed with rheumatic heart disease as compared to men, which could explain the decrease in mineralization ( 35 ). Moreover, it has been suggested that apoptotic and necrotic cell loss in heavily calcified AVs may lead to the development of prevalent dystrophic mineralization found in 83% of the histological AV specimens ( 36 ).…”
Section: Discussionmentioning
confidence: 97%
“…14 Females tend to have more severe aortic valve lesions compared to males. 16 Statistical analysis showed that sex was not associated with RHD severity (p=0.235). According to Lubega et al 17 there is no association between sex and tricuspid regurgitation, mitral stenosis severity.…”
Section: Discussionmentioning
confidence: 97%